Prediction Of Cutting Force By Numerical Solution And Statistic Method In End-Milling Operation. - K., Kadirgama; M. M., Noor; N. M. Zuki, N. M.; M. R. M., Rejab (2008)
The present paper discusses the development of the first order models and finite element analysis for predicting the cutting force produced in end-milling operation of modified AISI P20 tool steel. The first order cutting force equations are developed using the response surface methodology (RSM) to study the effect of four input cutting parameters (cutting speed, feed rate, radial depth and axial depth of cut) on cutting force. The cutting force contours with respect to input parameters are shown and the predictive models analyses are performed with the aid of the statistical software package Minitab. The predictive models in this study are believed to produce values of the longitudinal component of the cutting force close to those readings recorded experimentally with a 95% confident interval. Explicit code Thirdwave AdvantEdge has been used to estimate cutting and thrust forces. These estimated results are compared with experiments performed in this study and predictive model developed in this paper. The result from the simulation results are agreed with experimental value and predictive value from RSM.